1975
DOI: 10.1021/jf60197a022
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of (+)-trans- and (+)-cis-resmethrin in rats

Abstract: UEDA, GAUCHAN, CASIDA acids, terpene carboxylic acids and their glucuronides, and terpene alcohols as their glucuronides or sulfates. About 2% of the 14C appears as expired products, probably 14CC>2, and this portion arises from methyl, chloromethyl, or dichloromethyl substituents in the original toxaphene components. On the assumption that most of the toxaphene components are polychlorobomanes related to the identified 2,2,5-endo,6-exo,8,9,10-heptachlorobornane and in light of the extensive or even complete m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

1976
1976
1998
1998

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 11 publications
3
35
0
Order By: Relevance
“…In accord with the in vitro studies, in vivo experiments revealed that ( + )-cis-resmethrin gave rise to at least two unidentified ester metabolites in rat feces (20). Feces of rats contained three ester metabolites (I-III) of (+) -cis-fenothrin which are never or hardly derived from (+) -transfenothrin.…”
Section: Metabolism In Mammalssupporting
confidence: 62%
See 2 more Smart Citations
“…In accord with the in vitro studies, in vivo experiments revealed that ( + )-cis-resmethrin gave rise to at least two unidentified ester metabolites in rat feces (20). Feces of rats contained three ester metabolites (I-III) of (+) -cis-fenothrin which are never or hardly derived from (+) -transfenothrin.…”
Section: Metabolism In Mammalssupporting
confidence: 62%
“…An appreciable amount of tritium from allethronyl-3H (+ )-trans-chrysanthemumate was not recovered in the rat excreta (21,22). Incomplete excretion was also observed in the acid moiety of resmethrin, 70-73% of the radiocarbons being recovered during 6-day intervals (20). A substantial amount of the radioactivity was found in feces in every compound tested regardless of the dosage, and enterohepatic circulation may play some role, as in the case of resmethrin (17) and proparthrin (19) .…”
Section: Metabolism In Mammalsmentioning
confidence: 93%
See 1 more Smart Citation
“…The less desirable properties of chlorinated hydrocarbon insecticides are associated with their lipophilicity and inert chemical structures so that they are stored in the fatty tissues of organisms rather than being metabolized and eliminated. Although pyrethroids are similar to the chlorinated hydrocarbons in some of their physical properties, much evidence from research in the past decade (59)(60)(61)(62)(63)(64)(65)(66)(67)(68) suggests that the structural features of pyrethroids render them susceptible to mammalian detoxification systems, so that by one or more of several possible pathways they are rapidly converted to more polar compounds and are excreted in the urine or feces.…”
Section: Physical Properties Of Pyrethroids and Other Insecticidesmentioning
confidence: 99%
“…Thus, an elucidation of these features was undertaken using a pyrethroid insecticide tetramethrin [Neopynamin,3,4, MATERIALS AND METHODS…”
Section: Introductionmentioning
confidence: 99%